ANALYSIS OF SEISMICITY OF THE RA AND THE ADJACENT AREAS OF ARMENIAN HIGHLANDS FOR THE PERIOD OF 01.01.2000–23.10.2011 (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The Armenian highlands are characterized by the presence of potentially seismic zones that form the level of seismic hazard in the territory of the Republic of Armenia. In particular, the Van strong earthquake (M=7.2) on October 23, 2011 was manifested in Yerevan by seismic shaking (J=5–6 points). From this point of view, the analysis of the seismic-geodynamic situation in the study area during the given earthquake preparation is of particular interest. This stage of the analysis is devoted to the study of M≥ 4.0 seismicity of the region with coordinates (φ°Ν 38.0–42.0; λ°Ε 42.0–48.0) for the time period 2000–2011. The analysis of the spatio-temporal distribution of earthquakes with a magnitude of M ≥ 4.0 makes it possible to distinguish chronological chain series of epicenters associated with the seismogeodynamics of the Van focal zone. In particular, we have identified stages (2001–2003 and 2011), in which the seismicity course (M ≥ 4.0) confirms a certain relationship between the southwestern (Van) and northeastern (Zaqatala) focal zones of the studied area.
Keywords: seismic hazard assessment; earthquake map; seismicity; Van focal zone; seismological data; spatio-temporal distribution of earthquake epicenters